Comparative study between deep-fat frying and air frying of sweet potato perkedel - Abdul Rahman, Nur Syuhadatul Akmal; Malik, Nur Hafizah (Enhanced Knowledge in Sciences and Technology, 2023)
For the production of delicacies like fried perkedel, air frying is being promoted as a healthy substitute for deep-fat frying. In air frying, uncooked coated perkedel are heated in hot air that contains tiny oil droplets, dehydrating the perkedel and attempting to give the features of traditionally manufactured perkedel, but with a significantly lower level of fat absorbed in the product. This study aims to (1) produce sweet potato perkedel using deep-fat frying and air frying techniques, (2) investigate the physical properties of sweet potato perkedel made using deep-fat frying and air frying techniques, and (3) determine the sensory properties of sweet potato perkedel made using deep-fat frying and air frying techniques. Despite the fact that the air-frying process allows for the manufacture of fried items with lesser fat content, the slower temperature evolution also led to lower rates of moisture loss and colour development reactions. Longer processing durations are therefore required in order to potentially generate air-fried perkedel with moisture contents and a distinctive colour similar to those of deep-fat-fried perkedel. The two methods of frying also produced foods with markedly different textures in terms of their hardness; and sensory qualities. The industry could consider and view at air-fried perkedel as a healthy substitute for deep-fried perkedel, nevertheless.